Manipulating Orientation of Silicon Carbide Nanowire in Polymer Composites to Achieve High Thermal Conductivity. Issue 17 (12th July 2017) - Huang, Yun; Hu, Jiantao; Yao, Yimin; Zeng, Xiaoliang; Sun, Jiajia; Pan, Guiran; Sun, Rong; Xu, Jian‐Bin; Wong, Ching‐Ping
Abstract : Highly thermally conductive polymer composites have received considerable attention, along with development of electronic devices toward being more integrated, miniaturized, and functionalized. However, traditional polymer composites cannot meet the requirement of achieving higher thermal conductivity at relatively low filler loading. Herein, manipulating orientation of silicon carbide nanowire (SiCNW) in epoxy composites by coating method is reported to achieve high in‐plane thermal conductivity (10.10 W m −1 K −1 ) at extremely low filler loading (5 wt%), while it is only 1.78 and 0.30 W m −1 K −1 for epoxy/random SiCNW composite and epoxy/silicon carbide nanoparticle composite. Several models are employed to demonstrate that a good orientation and high aspect ratio of SiCNWs contribute to form heat transfer networks in the composites. This provides a promising future for thermal‐management materials, which are widely applied to electronic packaging, aerospace field, and medical engineering. Abstract : The SiC nanowires construct oriented thermally conductive paths by coating method. The fabricated composites exhibit a thermal conductivity of 10.10 W m −1 K −1 at 5 wt% loading, which is much higher than that of epoxy/random SiC nanowire (1.78 W m −1 K −1 ) and epoxy/SiC nanoparticle composites (0.30 W m −1 K −1 ). Manipulating orientation of 1D fillers sheds a light for thermally conductive polymer composites.